Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/jfmk6030066
|View full text |Cite
|
Sign up to set email alerts
|

Functional Translation of Exercise Responses from Exercise Testing to Exercise Training: The Test of a Model

Abstract: Exercise prescription based on exercise test results is complicated by the need to downregulate the absolute training intensity to account for cardiovascular drift in order to achieve a desired internal training load. We tested a recently developed generalized model to perform this downregulation using metabolic equivalents (METs) during exercise testing and training. A total of 20 healthy volunteers performed an exercise test to define the METs at 60, 70, and 80% of the heart rate (HR) reserve and then perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The talk test is commonly used as a surrogate for maximal testing exercises due to its simplicity, validity, and easy determination of exercise intensity in several populations. It is defined as a subjective measure of exercise intensity which has come to be accepted as an alternative to objective measures (%HRR, %VO 2 max) for exercise evaluation and prescription [12,15]. The rating of perceived exertion (RPE), defined as an alternative method to more technological and physiological measurements, holding some insights into accumulated fatigue is a widely accepted method for measuring intensity during exercise [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The talk test is commonly used as a surrogate for maximal testing exercises due to its simplicity, validity, and easy determination of exercise intensity in several populations. It is defined as a subjective measure of exercise intensity which has come to be accepted as an alternative to objective measures (%HRR, %VO 2 max) for exercise evaluation and prescription [12,15]. The rating of perceived exertion (RPE), defined as an alternative method to more technological and physiological measurements, holding some insights into accumulated fatigue is a widely accepted method for measuring intensity during exercise [16].…”
Section: Introductionmentioning
confidence: 99%
“…These components play a critical role in determining one's overall well-being and health status. To gauge these facets of physical fitness accurately, various testing protocols have been established, including the Balke protocol [21], Ruffier test [22], and the talk test [12,15]. A comprehensive assessment of physical fitness parameters provides valuable insights into the holistic impact of physical activity and outdoor activities like walking on individual health and well-being [23].…”
Section: Introductionmentioning
confidence: 99%
“…Tyrrell et al [ 37 ] tested a recently developed generalized model [ 38 ] to downregulate absolute training intensity in order to account for cardiovascular drift and achieve the desired internal training load using METs during exercise testing and training. Comparing acute responses to three time-matched exercise regimens consisting of sprint interval training, high-intensity interval training, and vigorous continuous training, Benítez-Flores and colleagues [ 39 ] suggested that high-intensity interval training and vigorous continuous training accumulate the longest duration at near maximal intensities, which is considered a key factor in enhancing maximal oxygen uptake (VO 2 max).…”
Section: Introductionmentioning
confidence: 99%